Generación híbrida de energía eléctrica como alternativa para zonas no interconectadas - Guacaneme Moreno, Javier Antonio; Trujillo Rodríguez, César Leonardo; Peña Suesca, Rafael Antonio (Ingeniería, 2006)
This paper presents options that can be implemented for electric distribution in less developed remote areas, grid unconnected with poor reliability and power quality.Hybrid electrical generation was proposed from some renewal sources, solar, wind, hidroelectricity, or another which can be used to generate very near where it is used. More sophisticated turbines, new converter machines, energy increment demand, and political changes on market electricity, permits develop new generation and distribution systems which can lead some energy sources on time and optimal quantities as the load demand on energy services and basic power load.